Biogas stations Design in West Bank and GAZA city - Herebat, Yusuf; Salman, Mohammad; Sabateen, Ahmad (جامعة بوليتكنك فلسطين - طاقة, 2019)
نظرا لزيادة استهالك الطاقة الكهربائية في مناطق الضفة الغربية وقطاع غزة، ولمحدودية الطاقة الكهربائية المزودة لهذه المناطق، ونظرا لزيادة اعداد الحيوانات في الضفة الغربية وقطاع غزة، يمكن االستفادة من سماد هذه الحيوانات في انتاج الغاز الحيوي. يعتبر الغاز الحيوي الناتج من سماد الحيوانات والذي يتكون من غاز الميثان بنسبة 60% وغاز أكسيد الكربون بنسبة تتراوح بين )40-35( % مصدرا نظيفا إلنتاج الطاقة الكهربائية. هذا المشروع يوضح كمية الغاز الحيوي التي يمكن استخراجها من سماد 3 الحيوانات في الضفة الغربية وقطاع غزة، والتي تقدر بحدود 155.77 )مليون م /عام(، وتصميم محطات غاز حيوي في مدن الضفة الغربية ومدينة غزة، والتي يمكن من خاللها انتاج طاقة كهربائية بمقدار 520)ميجا واط ساعة(، والتي بدورها تساعد في تغطية النقص في الكهرباء. Recently, an increase in electricity consumption was observed in West Bank and Gaza Strip, and because of the limitation of supplied power electricity to these areas, and because of the increasing numbers of animals in West bank and Gaza strip, we found that we can use the waste of these animals in order to produce biogas. biogas considered as a clean source of electricity production.it consist of methane (60%) and carbon dioxide (about 35-40 %).This project illustrate the amount of production biogas from animals manure in West bank and Gaza trip ,which is estimated about 155.77 million meter^3/year),and design biogas stations in west bank cities and Gaza city, in which it is possible to produce the electrical power for about 520 MWh, which in turn helps to cover the shortage of electricity.
CD , no of pages 74 , طاقة 6/2019
Keywords: Biogas stations